Delays in Sovereign Debt Restructurings. Should we really blame the creditors? - Christoph Trebesch (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
Disorderly debt restructurings can be detrimental for debtor countries and creditors alike. This paper investigates delays in sovereign debt restructurings using a comprehensive new dataset since 1980. Why are some debt crises settled in just a few months, while others take many years? Have creditor coordination problems become more cumbersome in recent years? To answer these and other questions, the study provides ample case study evidence. Moreover, I apply semi-parametric duration models. The results indicate that holdouts, inter-creditor disputes and litigation explain some of the observed restructuring delays. However, government behaviour and political instability appear far more important in explaining lengthy restructurings. The volume of IMF credits has no systematic influence on the speed of crisis resolution.
Keywords: F34; F51; C41; 330; Debt Crises; Debt Restructuring; Duration Models